Beyond shifting wealth : perspectives on development risks and opportunities from the global south - Organisation for Economic Co-operation and Development. Development Centre (OECD Development Centre, 2017)
Emerging and developing countries have grown faster than advanced countries since the 2000s. This shifting weight of global economic activity from 'the West' to 'East and South' is referred to as 'shifting wealth'. But in recent years, a number of factors, such as lower commodity prices, seem  to have brought this movement to a pause. Is the period of rapid growth in the emerging world over? This anthology takes stock of the situation and goes beyond the 'shifting wealth' narrative. It offers a forward-looking perspective on global risks and development opportunities over the next 15 years. It collects the perspectives of thought leaders from developing and emerging economies, offering their views and solutions on the most pressing global development challenges.The first chapter provides the OECD Development Centre's analysis of major development trends. These trends include: slowing growth in China, the end of the commodity super cycle, increasing difficulty accessing global financial markets, demographic transitions, faltering job creation, rapid urbanisation, the negative effects of climate change and conflict and security. These challenges also provide development opportunities. Twelve thought leaders and development practitioners from the global South explore these opportunities in four thematic chapters. They deal with issues such as: structural transformation in a new macro environment; inclusive societies; energy and the environment; and new forms of development co-operation.The anthology provides a starting point for dialogue and exchange on these risks and challenges as well as potential solutions to them.